Design of Normal Mode Helical Antenna for Seawater Application - Mohd Razali, Siti Harliza; Ngah, Razali; Kamardin, Kamilia; Yamada, Yoshihide (International Journal of Integrated Engineering, 2023)
To overcome the substantial propagation loss in the ocean, a low frequency band should be chosen when contemplating radio wave communication. Then, the antenna used at the portable radio equipment should be very small compare to the wavelength. For the miniaturized antenna, the normal mode helical antenna (NMHA) is suitable because of achieving high efficiency. In this paper, design method of NMHA in the seawater condition (r=81, =4) is explained. The frequency bands of 100MHz and 15MHz are selected. The self-resonant structures are determined based on the theoretical equation. Electrical characteristics such as resonant frequency, input impedance, VWSR and antenna efficiency are obtained through simulation by FEKO simulator. Electromagnetic simulation model is formed by taking into account the practical experimental condition. At 100MHz and 15MHz, resonances are ensured for antenna diameter lengths of 6.83 cm and 12.2 cm respectively. Input resistance of 27.15 and 94.14, antenna efficiencies of -14.88dB and -26.27dB are achieved at 100MHz and 15MHz respectively.